The Effect of Varying Torrefaction Temperature on the Physical and Mechanical Properties of Briquettes Made from King Grass - Rifanida Rifanida; Adi Setiawan; Shafira Riskina; Abubakar Dabet; Alchalil Alchalil (Politeknik Negeri Lhokseumawe, 2023)
Indonesia is a country which has rich biological diversity. King grass (Pennisetum Purpupoides) is one of biological species which easily grow but has not yet been optimally used. This study examined the physical, mechanical, and thermal properties of bio-briquettes produced from king grass which has been torrefied at temperatures of 150˚C, 175˚C and 200˚C. Prior to torrefaction process, fresh king grass was chopped to a size 3 cm, dried under the sun for five days, and then put into the torrefaction reactor with a residence time of 45 minutes. The resulting solid product, i.e. bio-char was then pulverized and sieved to a particle size of 40 mesh, then mixed with 20% wt binder and stirred manually to reach homogeneous. Subsequently, a purposely made press machine was used to produce briquette at a pressure of 150 kg/cm2 followed by drying the product under the sun for three days. The briquette characterization employed several techniques including thermogravimetry analysis (TGA), differential scanning calorimetry (DSC), bomb calorimeter, and mechanical testing. The results showed that the calorific value of king grass increased from 3747 cal/g to 4346 cal/g after the torrefaction process at a temperature of 175˚C. The results of the proximate test showed that the fixed carbon content increased from 4.76% to 25.75% after the torrefaction process at a temperature of 175˚C. In terms of mechanical properties, it is known that the torrefaction process of king grass has significantly improved the friability, density and size stability. Overall, this study has succeeded in revealing the potential use of briquette products made from king grass as alternative fuel for co-firing at steam power plant